PERHITUNGAN INDEKS KONDISI BANGUNAN DAN ANALISIS BIAYA PERBAIKAN GEDUNG AKADEMI KEPERAWATAN PANTI RAPIH PASCA GEMPA (Studi Kasus : Bencana Gempa 27 Mei 2006) - Suparjo, Iih; Priyosulistyo, Hrc.; Sudarmoko, Sudarmoko (Civil Engineering Forum Teknik Sipil, 2009)
Earthquake disaster on May 27, 2006 has forced many buldings to terminate their service due to the severe damage the earthquake caused to the buildings components. Such damage requires renovation in order to restore the building performance and function. This research analyzed the renovation cost analysis for Panti Rapih Nursing Academy in Sleman Regency, Yogyakarta. This research related to building advisability after shaked by earthquacke based on the Condition Index. Analytical Hierarchy Process (AHP) was used for the analysis. Based on this method, the building Condition Index depends on two parameters. The first parameter is building component and sub component weight. The second is the damage degree and quantity, which was obtained by onsite visual assessment. This research included the analysis of renovation cost completed with factors influencing the cost based on the degree of the damage. The renovation cost was calculated by multiplying unit cost and quantity of works, which was obtained from onsite results of the direct survey. The unit cost used refered to official cost in Regency of Sleman, Yogyakarta. Finally, the result obtained were then compared to the cost computed by contractor. Analysis results showed that the Condition Index of Nursing Academy Building was 93,5394%, which was within low damages category. In theory, the cost to restore the building Condition Index (back to 100%) was Rp. 73.160.000,00. This amount was lower than the real cost of Rp 97.680.000,00 calculated by the contractor. Such difference may be due to the different method used when calculating the quantity and unit cost of works.